Kajian Hubungan Antara Fitoplankton dengan Kecepatan Arus Air Akibat Operasi Waduk Jatiluhur - Harsono, Eko (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTStudy on The Relationship Between Phytoplankton and Current Velocities due to Operationof Jatiluhur Reservoir. High abundance of phytoplankton may create oxygen depletionwithin water column, in which may also lead as a threat to the fisheries activities of floatingcage in the Jatiluhur reservoir. In addition, phytoplankton may also clog the filter within watertreatment plant that is currently using the water from Jatiluhur reservoir. The research objectivewas investigate effects of changing water current velocity to the abundance of phytoplanktonin the Jatiluhur reservoir. Phytoplankton, measured as chlorophyll-a, were sampled at 10 differentsampling points of 0, 4, 8 and 10 m depth. While current water velocities were calculated usingtwo-dimensional multilayer equation. The equation will calculate x and y axis current velocitieswithin different depth of the reservoir. Result shows that in the area in which the currentvelocities higher than 15 cm/s less phytoplankton would be found. These velocities found ifthe operation of water discharge from reservoir was more than 70 m3/s. The research suggeststhat discharging operation from reservoir can be used as an indicator for the early warningsystem for the fisheries activities in the reservoir.Keywords: Jatiluhur reservoir, current velocity, phytoplankton abundance, reservoir operation,two-dimensional multilayer equation